Evaluation of adhesion properties of lignin-epoxy adhesives in structural wood applications for automotive components. (October 2020) - Aniol, A; Grosse, T; Fischer, F; Böhm, S
The use of sustainable hybrid components is an important topic in lightweight automotive applications. Wood being a renewable material, when used in combination with other materials such as technical polymers, offers a high potential for producing hybrid components and the implementation of innovative lightweight automotive materials. The feasibility of wood-based hybrid automotive components strongly depends on the properties of the interface between wood, lignin as a renewable coupling agent, and technical polymers. This paper investigates the macromolecular reactions and the bonding area in biobased epoxy adhesives for a specific influence on the performance of structural automotive wood components. Therefore, a typical bisphenol A diglycidyl ether epoxy adhesive was modified with lignosulphonate to increase the penetration depth. The composites were characterized by thermogravimetric analysis coupled with Fourier-transform infrared spectroscopy to validate the crosslinking of the macromolecules and the thermal stability of the adhesive. In the next step, a layer-by-layer composite was built up with the biobased adhesive and 1 mm beech veneer. The bonding area was characterized by scanning electron microscopy and compression tests.